2021
DOI: 10.3389/fgene.2021.795669
|View full text |Cite
|
Sign up to set email alerts
|

Mating Stimulates the Immune Response and Sperm Storage-Related Genes Expression in Spermathecae of Bumblebee (Bombus terrestris) Queen

Abstract: Bumblebee queens have remarkable spermathecae that store sperm for year-round reproduction. The spermathecal gland is regarded as a secretory organ that could benefit sperm storage. Queen mating provokes substantial physiological, behavioral, and gene expression changes. Here, the transcriptomes of spermathecae were compared between virgins and mated queens of the bumblebee, Bombus terrestris L., at 24 h post mating. Differentially expressed genes were further validated by real time quantitative PCR and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In Acromyrmex echinatior and A. colombica leafcutter ants, the expression of two antimicrobial peptides – abaecin and defensin – is upregulated in the male reproductive organs (accessory glands and testes) and in the spermatheca of virgin and mated queens (Chérasse et al ., 2018). Furthermore, in the bumble bee B. terrestris , defensin was upregulated in the spermatheca following mating (Guo et al ., 2021). Second, experimental studies have convincingly demonstrated that male and female reproductive tissues display antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…In Acromyrmex echinatior and A. colombica leafcutter ants, the expression of two antimicrobial peptides – abaecin and defensin – is upregulated in the male reproductive organs (accessory glands and testes) and in the spermatheca of virgin and mated queens (Chérasse et al ., 2018). Furthermore, in the bumble bee B. terrestris , defensin was upregulated in the spermatheca following mating (Guo et al ., 2021). Second, experimental studies have convincingly demonstrated that male and female reproductive tissues display antimicrobial activity.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…antimicrobial peptides), rather than via a generalized immune response which could potentially lead to sperm death. However, in B. terrestris , transcriptomic analyses recently showed that PO is upregulated in queen spermatheca after mating (Guo et al ., 2021), suggesting that antimicrobial strategies may differ among social insects depending on their specific life histories. For example, bumble bee queens usually have much shorter reproductive lifespans than ant queens.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most insects reproduce sexually, and the physiology and behavior of female insects change post mating [12][13][14][15][16][17]. After honey bee and bumblebee queens mate with drones, the expressions of immune-and sperm storage-related genes in spermathecae are significantly up-regulated [18,19]. Copulation also stimulates the activation of acquired immunity in the haemolymph of bumblebees, and the immunity is maintained continuously during diapause [20].…”
Section: Introductionmentioning
confidence: 99%